Inter-assay variability in the measurement of urinary C-terminal cross-linked telopeptide of type II collagen following anterior cruciate ligament reconstruction - Lachlan M. Batty; Kate E. Webster; Natasha Vassileff; Jereme G. Spiers; Haydn J. Klemm; Brian Devitt; Timothy S. Whitehead; Andrew F. Hill; Julian A. Feller (Osteoarthritis and Cartilage Open)
Objective: To compare urinary C-terminal cross-linked telopeptide of type II collagen (u-CTX-II) concentrations and trends as measured by two different commercially available enzyme-linked immunosorbent assays (ELISA) in a cohort of patients in the first year following anterior cruciate ligament (ACL) reconstruction. Design: 22 ACL-injured patients undergoing reconstructive surgery (mean age 25.2 (SD 8.0) years; 12 (54.5 ​%) male) had urine samples taken on the day of surgery (baseline) and at 6 and 12 months post-operatively. Concentrations of u-CTX-II were measured using the CloudClone® and the CartiLaps® ELISA. u-CTX-II concentrations were normalized to urinary creatinine (Cr). Results: The u-CTX-II concentrations were significantly different between the 2 assays at each timepoint (p ​≤ ​0.01). When measured using the CloudClone® Assay, mean (standard error) u-CTX-II concentrations were 26.5 (2.5) ng/mmol Cr, 29.4 (3.8) ng/mmol Cr and 40.6 (6.9) ng/mmol Cr at the baseline, 6-month and 12-month timepoints respectively. When measured using the CartiLaps® Assay, at the same respective timepoints, u-CTX-II concentrations were 981.2 (256.5) ng/mmol Cr, 867.0 (234.3) ng/mmol Cr and 764.3 (220.3) ng/mmol Cr. Concentrations of u-CTX-II using the CloudClone® Assay increased with time (p ​= ​0.04). Concentrations of u-CTX-II using the CartiLaps® Assay decreased over time (p ​= ​0.2). Conclusion: Using two commercially available assays, u-CTX-II differed significantly in terms of both concentration and trends in the first year following ACL reconstruction. The specific assay used is critical to consider when interpreting results and has implications for pooling data and meta-analysis.